The unexplored mechanism of antitumoral effect of pirfenidone in melanoma cells - Melissa Marchese; Gilda La Regina; Rachele Amato; Gianmarco Bertoni; Jessica Ruzzolini; Daniele Martinucci; Laura Papucci; Silvia Peppicelli; Francesca Bianchini (Scientific Reports)
Abstract Melanoma is still one of the most aggressive cancers, with global incidence and mortality rates expected to rise significantly by 2040. Surgical excision with adequate safety margins remains the standard treatment for primary cutaneous melanoma. However, the therapeutic approach to treat advanced stages or disease recurrence in melanoma is still challenging. Although initial responses to combined targeted therapies and immune checkpoint inhibitors often achieve clinical success, disease progression remains difficult to manage. Thus, there is an urgent need for novel and unexplored therapeutic strategies. Pirfenidone (PFD) is an antifibrotic drug approved for Idiopathic Pulmonary Fibrosis, with anti-inflammatory, and anti-oxidant properties. Its primary mechanism involves Transforming Growth Factorβ signalling downregulation, alongside with the suppression of cytokine and reactive oxygen species (ROS) release. Recently, it has been suggested that PFD may function as furin convertase enzyme inhibitor. Furin is involved in many physiological and pathological processes such as BRAF oncogene activation. In this study, we investigated the mechanisms of antitumoral effect of PFD in BRAF mutated human melanoma cell lines. Docking analysis revealed a close interaction between PFD and furin convertase active site. In vitro studies revealed that PFD reduced cell proliferation, clonogenicity, and invasiveness. Interestingly, the early antioxidant effect observed during PFD treatment was later replaced by a marked increase in ROS levels, along with p21 upregulation and induction of apoptosis. This multi-angle approach highlights a key role of furin in melanoma cell aggressiveness. Although, the present study lacks clinical data from melanoma patients, our observations suggest that PFD may represent a treatment option for metastatic melanoma cases that are resistant to conventional therapeutic interventions, through a drug repurposing approach.